The Metaphor of Gastrocentrism and the National Dilemma in Anglophone Cameroonian Poetry: The Examples of the Poetry of Mathew Takwi, Emmanuel Doh and Nol Alembong - Ngeh, Andrew T. (Advances in Social Sciences Research Journal, 2014)
The perception of the nation’s wealth as “a national cake” by both the rulers and the ruled has placed many African countries in a dilemma and this poses a challenge to nation-building. The nation is conceived and perceived by both the superstructure and the base in the diadic image of a perishable cake that if not eaten, will get bad. The cake as a metaphorical symbol is reminiscent of the Lacanian concept of lack and desire. As an absent centre around which major conflictual actions are enacted, the cake, like the nation is not respected, worshipped, served or maintained, but it is delicious, fragile, edible and appetizing. Analyzing Mathew Takwi’s People Be Not Fooled (2004), Doh’s Not Yet Damascus (2007) and Alembong’s Forest Echoes (2012) using Jacques Lacan’s concepts of lack and desire, this paper contends that the gastrocentric metaphor of the nation’s wealth as ‘cake’ which dominates the three collections places the Cameroonian/African nations in a dilemma and poses a challenge to nation-building. The rulers have, and the masses who lack, desire what the rulers have. These contradictions and conflicts are poeticized in the ideological formulations which find aesthetic expression in the poetic vision of Takwi, Doh and Alembong. The paper proposes a move toward a socialist nation where the nation’s wealth which encompasses socio-political and economic powers is linked to equity, nation-building and patriotism.